Estudo da liga cu-11,8al-xbe-0,3ti (x = 0,5; 0,6; 0,7) processadas termomecanicamente - Júnior., Manoel Quirino da Silva (2010)
Shape memory alloys have been object of diverse studies due to a vast fan of possible applications, such as: medical applications (materials for applications in dentistry and orthopedics), sensor (thermostats) and thermal-mechanics actuators (connections of tubes). The objectives of this work were the elaboration and characterization of Cu-Al shape memory alloys which contend beryl and titanium in the following percentages: Cu-11,8Al- XBe-0,3Ti (X = 0,5; 0,6 and 0.7% weight); and to analyze the viability of the thermomechanical process in these alloys. The influence of the variables about chemical composition, quench hardening, thermal cycling and the thermomechanical treatment in the transformation temperatures were investigated. It was possible to verify that the addition of small amounts of Be alters the matrix composition and, consequently, the transformation temperatures. For its time, Ti forms precipitated with amounts of copper and aluminum that inhibit the growth of the grain in the thermomechanical process. The alloys were cycled themically in a range among the temperature below of Mf and above of Af reaching stable values being evidenced a great thermal stability. The microstructural evolution before and after the thermomechanical process, the transformation temperatures and the thermal stability were characterized by the thermal analysis (DSC and DTA), scanning electron microscopy and x-ray diffraction. Under low speeds of cooling, the alloys show a decomposition of the β phase with formation of the γ2 and α phases, whereas in the fast cooling, the β phase passes to β1 without the presence of the other phases. With the increase of the percentile of Be, the γ2 phase increases and it maintains precipitated together in the matrix with rich particles of second phase in titanium. However, after ix lamination and temper, the γ2 phase is not presented anymore staying the dispersed particles of second phase in the matrix.